RAPPRESENTAZIONI DEL CORPO FEMMINILE E CRISI DEL SOGGETTO MASCHILE IN IO E LUI DI ALBERTO MORAVIA. - Kosanović, Nikolina Gunjević (Journal of Language & Literary Studies / Folia Linguistica & Litteraria, 2026)
This article examines the representation of the female body and its relationship to the crisis of masculine subjectivity in Alberto Moravia's novel Io e lui (1971). While Moravia has often been accused - particularly by feminist critics of the 1960s and 1970s - of portraying women as static, objectified figures within a predominantly male-centred narrative universe, this paper argues that Io e lui in fact destabilises the foundations of phallocentrism and exposes the instability of patriarchal identity. Through a close reading of the protagonist Rico's relationship with his wife Fausta and with the anthropomorphised figure of his penis ("Lui"), the article shows how Moravia dramatises the fragmentation of the male subject, highlighting the contradictions, anxieties and illusions that underlie male desire. The female body in the novel functions as a symbolic surface on which the male protagonist projects fantasies, desires, frustrations and fears. Fausta, once youthful and erotically idealised, now appears to Rico as a body marked by time - heavy, worn, "imbolsito" and therefore perceived as less desirable. Her transformation becomes, for Rico, not merely a sign of physical decay but a direct threat to the coherence of his own identity. The contrast between "Fausta di ieri" and "Fausta di oggi", repeatedly emphasised throughout the novel, crystallises the male protagonist's inability to accept the human dimension of change, ageing and corporeality. The female body becomes the repository of a loss that Rico cannot attribute to himself and thus he transfers the weight of his own crisis onto Fausta. This dynamic resonates strongly with Julia Kristeva's notion of abjection. For Kristeva, the abject is that which disturbs identity, system and order; it is what the subject must expel to maintain the illusion of a stable self. Fausta's changing body embodies precisely this disturbing materiality: it reminds Rico not only of the passage of time but also of the instability of his own self-image. Her flesh, marked by softness, folds and loss of firmness, triggers in him a reaction that oscillates between disgust and longing. At the same time, he persistently overlays her present form with the memory of her past beauty, reconstructing through imagination the youthful figure she no longer possesses. In this way, Fausta becomes simultaneously real and unreal, a palimpsest in which Rico reads the traces of his own desire and the failure of that desire to anchor him in a stable identity. The article argues that the tension between Fausta's present body and the memory of her past self establishes a key motif in the novel: the confrontation between reality and fantasy, between the corporeal and the imaginary. Rico does not see Fausta as she is; rather, he sees the discrepancy between what she was and what she has become. In this sense, the female body functions as a surface of inscription, much in line with Roland Barthes's reflections on the body as text. Rico reads Fausta's body not as a living organism but as a system of signs that either confirm or disrupt his perception of control. The past body is manageable and coherent; the present body is excessive, ungovernable, and therefore threatening. This dynamic reflects the crisis of the male subject that Jacques Lacan describes in relation to the split between the imaginary ego and the symbolic order. Rico is not a unified subject: he is divided between the selfimage he wishes to maintain and the unconscious forces of desire represented by "Lui". The penis, personified and endowed with its own voice and agency, becomes a figure of the Lacanian phallus - not the organ itself, but the signifier of power, identity and desire. Yet in Moravia's novel, this signifier is unstable, comic and tyrannical. Rather than securing authority, it undermines Rico's autonomy. The male protagonist attempts to assert control through rationality, discipline and artistic ambition, but "Lui" constantly interrupts, redirects and dominates him. This personification of the phallus makes explicit the illusion at the core of patriarchal subjectivity: the man does not control desire; desire controls him. In this respect, Io e lui constitutes a critique of the traditional foundations of patriarchy. The novel reveals that the male subject - supposedly rational, authoritative and dominant - is internally fragmented and dependent on forces he cannot understand or resist. Rico's conversations with "Lui" are filled with irony, self-deception and frustration. His inability to complete his film project, his recurring nightmares, his compulsive sexual fantasies and his humiliating behaviour (as in the episode at the newspaper kiosk) all point to the disintegration of the masculine ideal. Moravia lays bare the comic tragedy of a man who is dominated by the very symbol of dominance. This interpretation challenges earlier feminist readings that accused Moravia of misogyny. Critics such as Lilia Crocenzi and the duo Liliana Caruso and Bibi Tomasi argued that Moravia's writing belittles women and reinforces patriarchal norms by relegating female characters to passive roles. While such readings capture a recurrent surface structure in Moravia's fiction, they overlook the way in which Io e lui reverses the logic of domination. The novel does not simply present women as objects; rather, it exposes the male subject as an object - an object of his own desire, of his bodily impulses and of his fantasies. In this inversion lies Moravia's subtle critique: the female body is not the true site of weakness; the male ego is. The article further argues that Fausta does not embody moral inferiority or intellectual vacuity. On the contrary, she is the only character who remains consistent in her emotional orientation and unaffected by the internal conflicts that torment Rico. Although she is marginalised by Rico's narrative perspective, she emerges as a figure of authenticity: she acts out of affection, not compulsion; she seeks emotional connection rather than domination. In this sense, Moravia creates a contrast between Rico's fractured identity and Fausta's quiet resilience. Her subjectivity may not be expressed through explicit internal monologue, but it surfaces through her actions, her patience and her refusal to conform to Rico's idealisation. Furthermore, the novel's depiction of the domestic sphere - disorderly, chaotic and saturated with sensory excess - illustrates Michel Foucault's theory of disciplinary power. Rico expects Fausta to maintain both the household and her physical appearance according to codes of order and hygiene that are socially constructed rather than intrinsic. The tension between these expectations and Fausta's failure (or refusal) to meet them demonstrates how patriarchal norms are inscribed onto the female body and how women are judged not only aesthetically but morally based on their adherence to these norms. Yet Moravia subverts this mechanism: Fausta's "failure" destabilises Rico, not her. She remains emotionally intact; he collapses. Additionally, Luce Irigaray's theory of mimesis provides an interpretive lens for understanding the male desire to reproduce the idealised female image. Rico's obsession with the Fausta of ten years earlier reveals his attempt to freeze the female body in time, to force it into a constructed identity that serves his needs. The fact that the older Fausta no longer corresponds to this image is perceived by Rico not as a natural consequence of ageing but as a personal loss, a withdrawal of value. Moravia thereby exposes the violence implicit in the male gaze - the demand that the female body conform to an aesthetic norm that exists only in male fantasy. In its final sections, the article argues that Io e lui transcends its temporal context and offers insights into contemporary debates about gender, identity and sexuality. The novel portrays masculinity not as a stable essence but as a performance shaped by internal and external pressures. Rico is not a villain but a tragicomic figure whose struggle reflects broader cultural anxieties regarding male identity in the late twentieth century. His failure to reconcile his artistic aspirations, sexual impulses and relational responsibilities mirrors the fragmentation of modern subjectivity. Thus, the representation of the female body in Io e lui is neither ornamental nor secondary; it is central to the novel's exploration of the male psyche. Fausta's body, in its temporal transformations, forces Rico to confront the impermanence of his own desires and the illusions that underpin his self-conception. The female body becomes a mirror in which the male protagonist sees his own decline - physical, emotional and symbolic. In this way, Moravia's novel offers not a reaffirmation of patriarchal values but a critique of their fragility. In conclusion, this work situates Io e lui as a novel that challenges traditional interpretations of Moravia's relationship to feminism and offers a nuanced reading of his portrayal of women. It reveals the instability of male subjectivity, the limits of phallocentric logic and the complexity of the female body as both symbol and lived reality. By integrating literary analysis with theoretical frameworks drawn from psychoanalysis, feminist philosophy and cultural theory, the article demonstrates that Moravia's text remains profoundly relevant to contemporary discussions of gender, desire and the politics of the body.